Role of substituents on the reactivity and electron density profile of diimine ligands: a density functional theory based study - Kulkarni, Bhakti S.; Mishra, Deepti; Pal, Sourav (Journal of Chemical Sciences, 2013)
In this paper, we study the reactivity of diimines like 2, 2(')-bipyridine, 1, l0-phenanthroline and 1, 2, 4-triazines using density-based reactivity descriptors. We discuss the enhancement or diminution in the reactivity of these ligands as a function of two substituent groups, namely methyl (-CH3) group and phenyl (-C6H5) group. The global reactivity descriptors explain the global affinity and philicity of these ligands, whereas the local softness depicts the particular site selectivity. The inter-molecular reactivity trends for the same systems are analysed through the philicity and group philicity indices. The sigma-donor character of these ligands is quantified with the help of electron density profile. In addition, the possible strength of interaction of these ligands with metal ions is supported with actual reaction energies of Ru-L complexes.
Keywords: 2; 2 `-bipyridine; DFT; diimine; Reactivity descriptors; Ru-ligand interaction; substituent effects